2009
DOI: 10.1515/jpm.2009.025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sociodemographic and psychosocial characteristics on breastfeeding duration of mothers attending breastfeeding support groups

Abstract: Characteristics which positively influenced the duration of breastfeeding are the time when the decision to breastfeed was made, intended duration of breastfeeding, household income, and smoking during pregnancy. Mothers who attended BSG more often continued breastfeeding for at least six months if they decided to breastfeed after birth, intended to breastfeed for longer than six months, had higher monthly household income and did not smoke during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
2
3
0
2
Order By: Relevance
“…The enrolled and randomized women were more often of low socioeconomic status and more often had blue-collar employment, since they were more likely to have no plans for extended breastfeeding. This was in line with findings from our BRAVO pilot study [ 51 ] and previous studies, which showed an inverse relationship between breastfeeding rate and the socioeconomic status [ 57 59 ]. The decline rate of participants did not differ according to the women’s socioeconomic status.…”
Section: Discussionsupporting
confidence: 93%
“…The enrolled and randomized women were more often of low socioeconomic status and more often had blue-collar employment, since they were more likely to have no plans for extended breastfeeding. This was in line with findings from our BRAVO pilot study [ 51 ] and previous studies, which showed an inverse relationship between breastfeeding rate and the socioeconomic status [ 57 59 ]. The decline rate of participants did not differ according to the women’s socioeconomic status.…”
Section: Discussionsupporting
confidence: 93%
“…Breastfeeding rates (especially for 'exclusive breastfeeding') have not, however, reached their targets in several countries for example in the United Kingdom and the United States [2,3]. Thus, nursing studies have focused on the factors and interventions that affect the choice of feeding method, initiation of breastfeeding and duration [4-9]. One of the factors known to play a role is attitude towards infant feeding.…”
Section: Introductionmentioning
confidence: 99%
“…In Croatia there are currently over 200 breastfeeding support groups, led by community nurses and lay peer supporters (19). The first groups were established in the mid 1990's and studies have shown that mothers who attend these groups have higher breastfeeding rates (20). Despite the importance of breastfeeding support groups, none of the nursing textbooks assessed included the topics Fostering breastfeeding support groups and Training and support of community health workers.…”
Section: Discussionmentioning
confidence: 99%